2016
DOI: 10.1111/efp.12283
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of antifungal activity of Burkholderia pyrrocinia JKSH007 genetically modified with Bacillus subtilis Chi113 gene

Abstract: Previous studies showed that Burkholderia pyrrocinia JK-SH007 is a potential biocontrol agent of poplar canker disease. In this report, B. pyrrocinia JK-SH007 was genetically modified by introducing the Bacillus subtilis Chi113 gene to enhance its antifungal activity. The green fluorescence of B. pyrrocinia JK-SH007E1 can be detected because of its transformation with plasmid pHKT2-Chi113 containing a gfp reporter gene. Real-time quantitative PCR (qPCR) showed that the B. subtilis Chi113 gene was highly expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Experts argue that the risk of genetically engineered microorganisms on environment can be reduced to a minimum as long as standard operating procedures developed for genetic engineering and the corresponding laws and regulations are strictly followed (Davison, ; Han et al., ). In previous work by this group, it was confirmed that B. pyrrocinia isolate JK‐SH007 was an effective biocontrol agent for poplar canker disease (Ren, Li, Liu, Ye, & Wu, ), and the engineered bacterium B. pyrrocinia JK‐SH007E1 with foreign chitinase gene was constructed (He et al., ). The risks posed by the genetically engineered isolate of B. pyrrocinia JK‐SH007E1 required evaluation prior to release into the natural environment.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Experts argue that the risk of genetically engineered microorganisms on environment can be reduced to a minimum as long as standard operating procedures developed for genetic engineering and the corresponding laws and regulations are strictly followed (Davison, ; Han et al., ). In previous work by this group, it was confirmed that B. pyrrocinia isolate JK‐SH007 was an effective biocontrol agent for poplar canker disease (Ren, Li, Liu, Ye, & Wu, ), and the engineered bacterium B. pyrrocinia JK‐SH007E1 with foreign chitinase gene was constructed (He et al., ). The risks posed by the genetically engineered isolate of B. pyrrocinia JK‐SH007E1 required evaluation prior to release into the natural environment.…”
Section: Discussionmentioning
confidence: 89%
“…In previous work by this group, it was confirmed that B. pyrrocinia isolate JK-SH007 was an effective biocontrol agent for poplar canker disease (Ren, Li, Liu, Ye, & Wu, 2016), and the engineered bacterium B. pyrrocinia JK-SH007E1 with foreign chitinase gene was constructed (He et al, 2016). The risks posed by the genetically engineered isolate of B. pyrrocinia JK-SH007E1 required evaluation prior to release into the natural environment.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Burkholderia pyrrocinia JK-SH007, belonging to Bcc, is a strain that excels in promoting plant growth, inhibiting fungal growth [13][14][15], and degrading natural and synthetic contaminants such as the production of siderophores to degrade Fe(III) to usable Fe(II) [14]. Accordingly, engineered bacteria with enhanced antagonistic fungal resistance [16] and insect resistance [17] have been obtained via genetic modification. These two engineered B. pyrrocinia JK-SH007derived strains that we constructed utilize an inducible promoter, namely, the λ phage transcriptional promoter (PRPL), to express the chitinase gene [16] and the cry218 gene, encoding the insecticidal crystal protein Cry1Ac [17].…”
Section: Introductionmentioning
confidence: 99%